2012
DOI: 10.1186/1471-2296-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Child Health Care nurses conceptions of overweight in children: a qualitative study

Abstract: BackgroundRegistered Sick Children’s Nurses and District Nurses employed at Child Health Care centres are in a position to help prevent childhood overweight and obesity. Prevention of this challenging public health threat could be improved through having a better understanding of how this group of nurses perceives childhood obesity. The aim of this study was to elucidate the conceptions of childhood overweight, including obesity, among nurses working in Child Health Care.MethodA qualitative study using a pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 37 publications
2
73
0
Order By: Relevance
“…Across all three categories of articles, there was support for involving all relevant stakeholders (HCPs, children, parents and potentially other family members) in conversations regarding weight . While one lived experience paper suggested that HCPs should talk with parents without the child present , others recommended that HCPs speak directly to older children and teens , especially once they are old enough to participate in extra‐curricular physical activity activities .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all three categories of articles, there was support for involving all relevant stakeholders (HCPs, children, parents and potentially other family members) in conversations regarding weight . While one lived experience paper suggested that HCPs should talk with parents without the child present , others recommended that HCPs speak directly to older children and teens , especially once they are old enough to participate in extra‐curricular physical activity activities .…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested that HCPs use parents’ non‐verbal cues (e.g. facial expressions or body positioning) to indicate whether to continue discussions about weight , and potentially switch to other communication methods (e.g. written information) if parents appear angry or defensive .…”
Section: Resultsmentioning
confidence: 99%
“…The first part covered the CHC-nurses conceptions of childhood overweight [16]. An interview guide with open-ended questions was developed, relating to the aim of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research has added to the survey findings that school nurses perceived overweight and obesity as difficult issues to deal with when communicating with parents. In addition, the nurses perceived barriers in both a lack of parental recognition of their child's overweight being a problem and a lack of parental support for prevention efforts (Isma, Bramhagen, Ahlstrom, Ö stman, & Dykes, 2012; Morrison-Sandberg, Kubik, & Johnson, 2011). A study of audiorecorded counseling sessions between school nurses and overweight children indicated inadequate communication skills in the nurses (Magnusson, Kjellgren, & Winkvist, 2012).…”
Section: Introductionmentioning
confidence: 99%